Increasing Income Through Community Empowerment Programs in Kerawang Handicraft Crafts Industry Group in Dumati Village Kecamatan Telaga Biru Gorontalo District - Rusli Isa (Journal of International Conference Proceedings (JICP), 2018)
This study aims to describe: 1). Community Empowerment Program in the Bintang Terang handicraft industry group, 2) the role of filigree craft industry groups in increasing community income, the success of the Bintang Terang handicraft handicraft industry group program), supporting and inhibiting factors for the Bintang Terang handicraft industry. This research use descriptive qualitative approach. The research subjects were managers and program members of the filigree handicraft industry group. Data collection uses interviews, observation, and documentation. Researchers in conducting research are assisted by interview guidelines, observation guidelines, and documentation guidelines. Data analysis techniques used are data reduction, data presentation, and conclusion. Triangulation used is source and technique triangulation. The results of the study show that: 1) the program of the filigree handicraft industry group is a place to learn to gain knowledge and skills so that they get employment opportunities to increase income through the manufacture or manufacture of filigree, embroidery and brooches. 2) the role of the filigree handicraft industry group in binding community income is a benchmark for the success of the filigree handicraft industry group. 3) the success of the filigree handicraft industry group program, namely members have the knowledge, skills to make filigree designs, embroidery and brooches in increasing family income and welfare which is characterized by gaining employment opportunities, increasing members; income, good social relations. 4) supporting factors include cooperation between managers, members, suppliers of raw materials, markets, government; motivation; transparent; maintain trust and market demand a lot. The inhibiting factor is the lack of capital; sometimes there is a bad relationship between members, causing boredom; quiet market demand in certain months and the number of competitors. Recommendations for the Bintang Terang craftwork industry group program are to hold regular meetings, increase capital, and carry out promotions to areas that have not been reached. Keywords: Community Empowerment, Community Income